Applying Participatory Action Research (PAR) in Advancing Islamic Education - Hidayatulloh, Hidayatulloh (Pelangi (e-Journal), 2025)
The Participatory Action Research (PAR) approach offers a strategic alternative for developing Islamic education that is more inclusive and transformative. Unlike conventional research, PAR positions the community as the primary agent of change rather than merely a research subject. This article aims to explore the history, definition, key principles, and application of the PAR approach in the development of Islamic education. Through library research and qualitative content analysis, it is found that PAR provides active space for community participation in designing, implementing, and evaluating education based on local needs. PAR emphasizes the importance of reflection, collective action, and empowerment. In the context of Islamic education, PAR can revitalize values such as justice, consultation (shūrā), and reciprocity as ethical foundations for social transformation. This article recommends integrating PAR into community service programs, curriculum development, and efforts to improve the quality of Islamic education.